PENGARUH STRES KERJA TERHADAP KINERJA DENGAN DUKUNGAN SOSIAL SEBAGAI VARIABEL MODERASI (Studi Kasus Tim Penggerak PKK Kabupaten Rembang) (STIE YPPI Rembang, 2012)
The research aims to test the effect of work stress on performance with social support as a moderating variable in the study Mover Team Empowerment and Family Welfare (TP PKK) Rembang. This research uses the entire population of the members of Team Empowerment and Family Welfare Driving Rembang year period 2010 - 2015 as many as 58 people. The data analysis technique used is simple linear regression and Moderated Regression Analysis (MRA). Results of research refer that the work stress have an influence negative not significantto performance TP PKK Rembang, while work stress have an influence positive sifnificant to performance when moderated by social support.Keyword: work stress, social support, and performance